Psychiatry in Nigeria - Gureje, Oye (Int Psychiatry, 2003)
Nigeria is a huge country. It covers an area of 924 000 km(2) on the west coast of Africa. It has a population of about 110 million, which means that every one in six Africans is a Nigerian. It is a country of diverse ethnicity, with over 200 spoken languages, even though three of those are spoken by about 60% of the population. Administratively, it is divided into 36 states and operates a federal system of government, with constitutional responsibilities allocated to the various tiers of government – central, state and local. There are two main religions, Islam (predominantly in the north) and Christianity (predominantly in the south). However, a large proportion of the people still practise traditional religions exclusively or in addition to either Islam or Christianity.